PENGEMBANGAN CD PEMBELAJARAN INTERAKTIF BERBASIS KONSTRUKTIVISME BERBANTUAN MACROMEDIA FLASH 8 PADA MATERI GEOMETRI SMP - Tesi Kurnia (Departemen Matematika, 2021)
Learning media in schools have not facilitated students to learn actively. Therefore, an interactive learning CD was developed on the geometry in junior high school was developed to facilitate students in learning. This type of research is design research. The model in this study is the Plomp model which consists of three phases, namely preliminary research, development and prototyping phase, and assessment phase. At the preliminary research phase requires needs analysis, student analysis, curriculum analysis, and concept analysis. At the development and prototyping phase, the product is designed using macromedia flash 8 application Futhermore, the product will be evaluated to obtain valid criteria through self evaluation and expert review. After the product is declared valid, one to one evaluation and small group evaluation are carried out. The results of the analysis of the validity of the questionnaire obtainen a percentage of 87,89% with a very valid category. The results of the questionnaire analysis of student responses to one to one evaluation obtained a percentage of 90,83% with a very practical category and a small group evaluation obtained a percentage of 91,67% with a very practical category. It can be concluded that the development of constructivism based interactive learning CD in junior high school geometry material is valid and practical. Keywords— Interactive learning CD, Constructivism